A historicidade da pulsão e a transmissão da cultura - Viana, Ruth Arielle Nascimento (2020)
This research comes from a questioning about “transmission” in Psychoanalysis – this theme relates itself with the own Psychoanalysis’s transmission and, in a larger way, with the form that Psychoanalysis theorizes culture’s transmission. The fundamental thesis that authors like Sigmund Freud (1856-1939) and Jacques Lacan (1901-1981) have established about subject and culture’s constitutions have a relationship with the theme of transmission, through fundamentals categories to Psychoanalysis, like the Drive, in its inherent relation with the statute of what is unconscious. This research inquires about the question that it wouldn’t be possible to think the dimension of transmission (historical) of the human without the psychoanalitics’s interns contributions of the concepto of Drive in its intrinsic relationship with the form that operates with the temporality of it. Watching Jacques Lacan’s insistence in sustaining what would be in the center of freudians’s propositions about the subject and the culture – the Unconscious and the Drive – this research proposes itself to address, considering Lacan’s contributions in his work of “return to Freud” and the context of the discussion of transmission, the temporality, starting from this central category to Psychoanalysis – the Drive. Then, the research investigates the way of operation from Drive in its relation with time. We start from the hypothesis that the Drive, in its necessary interlacing with the proposition of the Unconscious, establishes fundamental relations with the form itself of transmission and that the study of the relationship between Drive, transmission and time can bring important contributions to Psychoanalysis’s advance in what it bets in a historical – and historicizing – dimension of the subject’s advent. In this way, we articulate important notions to Psychoanalysis, such as myth, fiction and trauma, in its relations with emergence’s conditions and the particular way of operation that constitutes metapsychology. We hope, with this research, to contribute for studies that, in several fields, face the dilemmas that are so present today in the debates around history and memory, fundamentaly culminating in a profound questioning of the notion of representation. In a closer definition, this research puts itself in a questioning field of transmission’s statute, searching to aprehend which consequences that notions that are vitals to the metapsychology – such as of Unconscious and Drive – can carry to the debate around transmission, historicity and time.